Evaluation of the Solomon Islands Rural Development Program - Neelim, Ananta; Vecci, Joseph (World Bank, Washington, DC, 2015)
The purpose of this report is to analyse the impacts of the Rural Development Programme (RDP) of the Solomon Islands. RDP is an initiative to facilitate development in rural Solomon Islands. It focuses on participatory development, demand-responsive provision of Government services and creation of a supportive economic environment for small-scale rural development to foster employment and income growth. As a part of this evaluation process, a follow up survey was conducted in eighty villages, equally distributed across four provinces (Choiseul, Malaita, Temotu and Western) between June and July 2013. In each village we utilised two survey instruments, a) a household survey which was administered on ten randomly chosen households and b) a second questionnaire administered on community leaders (which also included members of the RDP s subproject implementation committee). The data collected in the baseline survey, conducted between 2010 and 2011, was the main basis for comparison and subsequent impact evaluation.